宫颈癌筛查人群对自取样尿液 HPV 检测的接受度及 影响因素分析. - 李一凡; 秦川玉; 曾玺; 陆娅胶; 廖光东; 康乐妮; 杨英; 周敏; 郄明蓉; 杨春霞; 李静 (Practical Oncology Journal, 2025)
Objective The aim of this study was to explore the acceptance and influencing factors of self-collected urine samples for human papillomavirus (HPV) testing in cervical cancer screening among eligible women, and to provide scientific evidence for promoting this testing in low resource areas. Methods A population-based cross-sectional study was conducted from 2022 to 2023 at the Maternal and Child Health Hospital in Shuangliu district, Chengdu City Sichuan Province. The study subjects were women aged 21 to 69 years old, and a customized questionnaire was used to conduct general information and acceptance surveys on the participants. Results A total of 2, 062 women were included, with an average age of 51. 58±9. 34 years. Among them, 1, 501 (72. 79%) women believed that self-sampling urine was very easy. However, although 1, 333 (64. 65%) women were still willing to accept doctor sampling as a cervical cancer screening method, only 729 (35. 35%) were more willing to accept self-sampling urine HPV testing. Age, educational level, annual household income, awareness of HPV, HPV vaccination status, and a sense of shame about the doctor′s sampling process were all associated with the acceptance of self-collected urine HPV testing among women undergoing cervical cancer screening (P<0. 001) . The results of multivariate logistic regression analysis indicated that older women (OR= 0. 965, 95% CI:0. 951 -0. 979) and those who were not familiar with HPV (OR= 0. 760, 95% CI:0. 602-0. 961) were more likely to undergo self sampling urine HPV testing, while those with junior high school education (OR = 1. 330, 95% CI:1. 053-1. 682), high school education or above (OR= 1. 990, 95% CI:1. 401-2. 827), and a sense of shame towards the doctor′s sampling process (OR= 2. 314, 95% CI:1. 706 -3. 142) were more likely to undergo self sampling urine for HPV testing. Conclusions Most women believe that self sampling urine for HPV testing is very easy, but compared to doctor sampling, only some women choose to self sample urine for HPV testing. Key health education interventions should be carried out for older and lower educated populations to promote acceptance of urine HPV testing.